La cooperación para el desarrollo autonómica y local. Balance y tendencias - Illán Sailer, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
The present article summarizes the aid policy implemented by regional and local authorities in Spain over the last ten years. Such policy has been shaped by the big expansion in quantitative terms and by the efforts to improve it qualitatively, which has led to the achievement of strategic frameworks, especially visible in the autonomous regions. These efforts, together with those of the Spanish Secretary of State for International Cooperation are meant to improve aid coordination and, after all, the effectiveness of the decentralised aid.